Exergy analysis of novel integrated systems based on MHD generators. (6th May 2021) - Sheykhlou, Hosseyn; Jafarmadar, Samad; Rezaei, Razieh Abbasgholi
The present work concerns with the thermodynamic analysis of novel opened and closed magneto hydrodynamic organic Rankine cycles (MHD-ORCs). In this regard, the thermodynamic simulation of the integrated systems with the assumption of the constant stream velocity in the MHD generator has been performed. The impact of MHD input temperature, the electrode surface area, the plasma velocity, and the compressor isentropic efficiency on the overall performance of the combined cycles have been investigated. Moreover, exergy and thermal efficiencies of opened and closed MHD-based cycles have been calculated and achieved in optimal points as follows; 66.15%, 71.67%, 49.21%, and 39.77%, respectively.